2013
DOI: 10.1002/tea.21134
|View full text |Cite
|
Sign up to set email alerts
|

“What comes to mind when you think of science? The perfumery!”: Documenting science‐related cultural learning pathways across contexts and timescales

Abstract: In this paper, we explore the details of one youth's science-related learning in-and out-ofschool at the time of her participation in an ethnography of youth science and technology learning across contexts and over time. We use the Cultural Learning Pathways Framework to analyze the youth's interests, and the related sociocultural, historical, material, and affect-laden practices in which she and her family participated. The following question guided our analysis: How do everyday moments-experienced across set… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
84
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(87 citation statements)
references
References 44 publications
(48 reference statements)
1
84
0
2
Order By: Relevance
“…While in this first phase of research, we did not do a curiosity behavior comparison to scores; however, the psychometric results of the final selected items align with other ethnographic studies of science practices across settings -reinforcing the relevance of the items on SCILE scale to youth's everyday science activities. For example, a large research project (Bell, Bricker, Reeve, Zimmerman, & Tzou, 2013) based on an ethnographic study of a multicultural community of an elementary school found that children and their families selfreported an interest in mixing (Bricker & Bell, 2014) and in experimenting with things (Zimmerman & Bell, 2014), reinforcing the inclusion of two items: 'I mix things together to see what happens' and 'I experiment with stuff to see what will happen.' Given youth's interest in building, making, and tinkering (Bevan, Gutwill, Petrich, & Wilkinson, 2015;Wardrip & Brahms, 2015;Zimmerman & Bell, 2014), the two items 'I would like to invent something new' and 'I like to make things that no one else has made' fit well into the scale.…”
Section: Discussionmentioning
confidence: 98%
“…While in this first phase of research, we did not do a curiosity behavior comparison to scores; however, the psychometric results of the final selected items align with other ethnographic studies of science practices across settings -reinforcing the relevance of the items on SCILE scale to youth's everyday science activities. For example, a large research project (Bell, Bricker, Reeve, Zimmerman, & Tzou, 2013) based on an ethnographic study of a multicultural community of an elementary school found that children and their families selfreported an interest in mixing (Bricker & Bell, 2014) and in experimenting with things (Zimmerman & Bell, 2014), reinforcing the inclusion of two items: 'I mix things together to see what happens' and 'I experiment with stuff to see what will happen.' Given youth's interest in building, making, and tinkering (Bevan, Gutwill, Petrich, & Wilkinson, 2015;Wardrip & Brahms, 2015;Zimmerman & Bell, 2014), the two items 'I would like to invent something new' and 'I like to make things that no one else has made' fit well into the scale.…”
Section: Discussionmentioning
confidence: 98%
“…A synthesis of prior research highlights the relationship between identity and science learning. Bricker and Bell (2014), for instance, argued that Science-Technology-Engineering-Mathematics (STEM) related learning outcomes are influenced by entities such as values, cultural norms, identities, and interests. Nasir (2002) contended that learning is as much about becoming as it is about knowing.…”
Section: The Importance Of Identity For Learningmentioning
confidence: 99%
“…Therefore, we drew upon social practice theory 2 to determine how youth negotiate settings and author their identities within the specific affordances of a social context to understand the socially constructed nature of youth's identity during learning conversations at a science camp (Bricker & Bell, 2014;Holland & Lave, 2009;Johnson, Brown, Carlone, & Cuevas, 2011). Holland et al (1998) …”
Section: Theoretical Framingmentioning
confidence: 99%
“…More recently, researchers and educators have recognized the flaw in their teaching methodologies and-as indicated by the growing number of studies regarding social/cultural aspects in STEM education-have taken strides towards integrating social trends and student culture in hopes of enhancing student interest and motivation (hence why 20 of the 119 studies included in our review directly consider either social or cultural trends as means for enhancing interest). Their research was often driven by the question: How do everyday moments-experienced across settings, pursuits, social groups, and time-result in scientific learning, expertise development, and personal identification (Bricker & Bell, 2013)?…”
Section: Theme 3: Social/cultural Based Motivation (N=20)mentioning
confidence: 99%